Dinitrosopiperazine‐decreased PKP3 through upregulating miR‐149 participates in nasopharyngeal carcinoma metastasis. Issue 12 (19th September 2018) - Li, Yuejin; Ju, Kunyu; Wang, Weiwei; Liu, Zheliang; Xie, Haitao; Jiang, Yuan; Jiang, Guanmin; Lu, Jinping; Dong, Zigang; Tang, Faqing
Abstract : Nasopharyngeal carcinoma (NPC) has a high metastatic clinicopathological feature. As a carcinogen factor, N, N′‐dinitrosopiperazine (DNP) is involved in NPC metastasis, but its precise mechanism has not been fully elucidated. Herein, we showed that DNP promotes NPC metastasis through upregulating miR‐149. DNP was found to decrease Plakophilin3 (PKP3) expression, further DNP‐decreased PKP3 was verified to be through upregulating miR‐149. We also found that DNP induced proliferation, adhesion, migration and invasion of NPC cell, which was inhibited by miR‐149‐inhibitor. DNP may promote NPC metastasis through miR‐149‐decreased PKP3 expression. Therefore, DNP‐increased miR‐149 expression may be an important factor of NPC high metastasis, and miR‐149 may serve as a molecular target for anti‐metastasis therapy of NPC.